A novel anion-radical salt (N-Et-2.5-di-Me-Pz)(TCNQ)₂ (Pz is pyrazine) - Ziolkovskiy, D.V.; Kazheva, O.N.; Shilov, G.V.; Dyachenko, O.A.; Kravchenko, A.V.; Khotkevich, A.V.; Starodub, V.A. (Functional Materials, 2006)
Synthesis, structure and properties of the new tetracyanoquinodimethane anion-radical salt (ARS) having the composition (N-Et-2.5-di-Me-Pz)(TCNQ)₂ (Pz is pyrazine) are reported. The compound has a layered structure where conducting anion-radical layers formed by TCNQ alternate with non-conducting cation layers along the a axis. The charges of TCNQ particles in the stack alternate, i.e. are localized appreciably, which can account for a rather unusual temperature dependence of electric resistance. Such a peculiarity of structure renders to the ARS electronic system a somewhat two-dimensional character that is unusual for TCNQ ARS and agrees with the electrophysical measurements. Описаны синтез и свойства новой анион-радикальной соли (АРС) тетрацианохинодиметана состава (N-Et-2,5-di-Me-Pz)(TCNQ)₂ (Pz - пиразин). Соединение имеет слоистую структуру, в которой проводящие анион-радикальные слои, образованные TCNQ, чередуются с непроводящими катионными слоями вдоль оси a. 3аряды частиц TCNQ в стопках альтернируют, то есть, заметно локализованы, что может быть причиной необычной температурной зависимости электросопротивления. Такая особенность структуры придает электронной системе АРС определенную двумерность, необычную для АРС TCNQ, и согласуется с результатами электрофизических измерений. Описано синтез та властивостi нової анiон-радикальної солi (АРС) тетрацiанохiнодiметану складу (N-Et-2,5-дi-Me-Pz)(TCNQ)₂ (Pz - пiразин). Сполука має шарувату структуру, в якiй провiднi анiон-радикальнi шари, утворенi TCNQ, чередуються з непровiдними катiонними шарами уздовж осi a. 3аряди часток TCNQ в стопках альтернують, тобто, суттєво локалiзованi, що може бути причиною незвичайної температурної залежностi електроопору. Така особливiсть структури додає електроннiй системi АРС певну двомiрнiсть, незвичайну для АРС TCNQ, i добре узгоджується з результатами електрофiзичних вимiрiв.